What Does the Body Communicate With Postural Oscillations? A Clinical Investigation Hypothesis - Buscemi, Andrea; Campisi, Santi Scirè; Frazzetto, Giulia; Petriliggieri, Jessica; Martino, Simona; Ambramo, Pierluca; Rapisarda, Alessandro; Maldonato, Nelson Mauro; Di Corrado, Donatella; Coco, Marinella (Frontiers in Psychology, 2021)
The evolution of the foot and the attainment of the bipedia represent a distinctive characteristic of the human species. The force of gravity is dissipated through the tibial astragalic joints, and the movement of the ankle is manifested on a sagittal plane. However, this is in contrast with other studies that analyse the straight station in bipodalic support of the body. According to these studies the oscillations of the body, dissipated by the articulation of the ankle, are actually greater on a frontal plane rather than on a sagittal plane. Probably, this can be deduced by analysing the concept of "cone of economy and equilibrium"; a cone that has as its base the oscillations described by the 360° movement performed by the head and as its apex the support polygon defined by the tibio-astragalic articulation. The purpose was to evaluate a kind of communication between the oscillations of the cone of economy and equilibrium and the main sphere of somatic dysfunction (structural, visceral or cranial sacral), assessing the reliability of the "fascial compression test" . The implications of this connection have been considered, while grounding the hypothesis in the ability of the human body to maintain its centre of mass with minimum energy expenditure and with the minimum postural influence. At the same time, the fascial compression test provides a dominant direction of fascial compartments in restriction of mobility.